Influence of Human Capital on the Development of Tourism Industry - NAKIPOVA, Gulmira; ARYNOVA, Zhanna; KUNYAZOV, Erlan; BEREZYUK, Valentina; ZHUNUSOVA, Aliya; SYZDYKBAYEVA, Bakyt (Journal of Environmental Management and Tourism; Vol 12 No 6 (2021): JEMT Volume XII Issue 6(54) Fall 2021, 2021)
Human capital is the main economic resource that increases the country's GDP, which has become the main productive and social factor in the development of the economy and is a major supplier of knowledge in achieving sustainability and competitiveness in the world market. It is not only about generating knowledge, but also about the opportunities that the industry has in integrating this new knowledge into its products, services and processes and disseminating it to people through education, training and information. The importance of the knowledge, competencies and skills of workers is increasing due to the specific characteristics of the product and services offered by the tourism sector. The aim of the study is to analyze the main indicators of the tourism industry, which consider the capabilities of human capital as a key factor in determining competitiveness. While human capital is not always emphasized when assessing competitiveness in the tourism industry, human capital capacity is a key factor. In many countries, the competitiveness of human capital in tourism is lower than desired, providing opportunities for additional investment in competitiveness through education and better labor market practices.